Quantitative assessment of the resource recovery potential from end-of-life lead-acid batteries based on consumption patterns: A case study from China - Huimin Hou; Wei Wei; Sui Zhang; Shuo Zhu; Zichen Di; Fangqin Cheng; He Xu; Junli Liu (Environmental Impact Assessment Review, 2026)

Tracking the pattern of material metabolism and environmental impacts of phosphogypsum utilization in China - Huimin Hou; Yumeng Yang; Zichen Di; Haibin Wu; Fangqin Cheng; He Xu (Journal of Cleaner Production, 2026)

Comparative genomics reveals that Bifidobacterium longum subsp. longum BZG4 alleviates constipation in mice via synergistic xylooligosaccharide - YaXin Gu; Qingqiu Ye; Xin Feng; Junzhu Li; Zichen He; Ming Zhang; Yanling Hao; Zhengyuan Zhai (Food Bioscience, 2026)

Spring extreme heat in the Indochina Peninsula enhances the prediction skill of summer precipitation in Central China - Yihua He; Wei Lou; Cheng Sun; Menghao Dong; Zichen Song; Linfeng Shi; Yibing Tong (Atmospheric Research, 2026)

QUEFTS model-based estimation of potato nutrient requirements in Western Inner Mongolia: a multi-site and multi-year assessment - Jianwei Hou; Cunfang Xing; Zichen Bai; Jun Zhang; Tingting Zhang; Junmei Liang; Hao An; Huiqing Lan; Hongyan Gao; Yu Duan; Ping He (Plant and Soil, 2026)

Seasonal dynamics of Gulf Stream–Kuroshio SST coupling: the role of hemispheric atmospheric teleconnections - Menghao Dong; Cheng Sun; Linfeng Shi; Wei Lou; Zichen Song; Yihua He; Yibing Tong (Climate Dynamics, 2026)

Identification of volatile and non-volatile components of two lemons based on sensory characteristics, electronic sensing evaluation and untargeted metabolomics - Baogan He; Long Wan; Zengyi Song; Zichen Ni; Xutong Xiang; Luqi Yin; Binbin Wei; Liming Zhang; Xiaofan Wang (Food Control, 2026)

Changes in persistent anticyclonic circulation across Eurasian continent and its linkage with extreme heatwaves - Yibing Tong; Cheng Sun; Wei Lou; Menghao Dong; Linfeng Shi; Zichen Song; Yihua He (Global and Planetary Change, 2026)

An initial subsystem stiffness-integrated seismic performance optimization approach for super high-rise frame-core tube structures using generalized models - Xiao Lai; Zheng He; Jian Yang; Zichen Li (Soil Dynamics and Earthquake Engineering, 2025)

Hetero-structured hydrogel with transition layer: Achieving synergistic sensing-actuating integration for intelligent ship - Bingchen Zhou; Tianzong Jiang; Yanqi Yin; Zewei Sun; Zichen Lu; Shili Gai; He Ding; Piaoping Yang (Chemical Engineering Journal, 2025)

Deep reinforcement learning control as an innovative approach for urban drainage systems: review and prospects - Zichen He; Wenchong Tian; Jiaying Wang; Hexiang Yan; Kunlun Xin; Tao Tao (Water Research, 2025)

Significant insights of CaO2 promoting heavy metal complexes removal during a plasma process - Meiqian Lu; Rong Li; Zichen Wang; Yue Liu; Guodong Zhang; Qiuling Ma; Jian Zhou; He Guo; Tiecheng Wang (Journal of Environmental Management, 2025)

Global teleconnection of concurrent dry and wet events revealed by climate network - Menghao Dong; Cheng Sun; Wei Lou; Linfeng Shi; Zichen Song; Yihua He; Yibing Tong (Climate Dynamics, 2025)

Genetically engineered hybrid membrane-coated nanoparticles enable triple activation of dendritic cells for synergistic bladder cancer immunotherapy - Jian Wu; Zhiqiang Chen; Haojie Shang; Yonghua Tong; Wen Deng; Yu He; Xiaozhuo Ba; Zichen Zhong; Yongke Bai; Tao Ye; Xiaoqi Yang; Kehua Jiang; et al. (Chemical Engineering Journal, 2025)

Adsorption performance and mechanism of HFO/pumice composites for phosphate in water - Jian Huang; Xianjin Qiu; Hua Zhang; Chenxi Zhang; Zhuoyi Lu; Tao Luo; Chunhua He; Jiamei Zhang; Zichen Shuai (Limnologica, 2025)

Determination and quantitative evaluation of early postharvest hidden damage in fresh strawberry fruit based on coupling of dynamic finite element method and response surface methodology - Jie Guo; Yufei Liu; Manoj Karkee; Xuping Feng; Zichen Huang; Yuwei Wang; Wenkai Zhang; Xiaoli Li; Yong He (Computers and Electronics in Agriculture, 2024)

Bacterial phylotypes associated with rock-dwelling Umbilicaria Lichens from Arctic/Subarctic areas in North America and Northern Europe - Zichen He; Takeshi Naganuma; Merry Sailonga Faluaburu; Ryosuke Nakai; Hiroshi Kanda; Masaki Uchida; Satoshi Imura; Martin W. Hahn (Polar Biology, 2024)
The diversity of bacteria associated with lichens has received increasing attention. However, studies based on next-generation sequencing of microbiomes have not yet been conducted in the Arctic and Subarctic regions. In this study, rock-dwelling lichens belonging to the Umbilicariaceae family were sampled from the Arctic and Subarctic biological zones. The primary research purpose was to undertake a comparative investigation of the bacterial composition and diversity, identify potential indicators, and explore their potential metabolic pathways. 18S rRNA gene sequences of the fungal partner belonging to the genus Umbilicaria (Ascomycota) and the algal partner affiliated with the lineage Trebouxia (Chlorophyta). Comparing Umbilicaria spp. with a previous study in the Antarctic zone, the fungal partners were more inclined to cluster by sampling region. Operational taxonomic units (OTUs) were established based on a predetermined similarity threshold for V3-V4 sequences, which were ascribed to 19 bacterial phyla, and ten of them were consistently present in all samples. The most distinct zonal indicator genera based on OTU frequencies from Arctic and Subarctic lichens were Capsulimonas (Armatimonadota) and Jatrophihabitans (Actinomycota), respectively. Although the Subarctic zone had higher biodiversity and species richness based on alpha-diversity, the beta-diversity showed that the main species of bacterial communities were not significantly different, and the predictions of metabolic pathways based on the bacterial microbiome in lichen samples from the two zones were similar. These findings provide evidence that the geographical and/or bioclimatic environment and the different lichen-forming fungal species mainly and partially influence bacterial microbiomes and metabolic pathways.

Migration mechanisms of 90Sr and 137Cs on terraces - Yongjing Guan; Zichen Guo; Wu Chen; Kaidi Fan; Hua He; Liangjia Cui; Chunping Huang; Xianwen He; Zeyue Xu; Jiajia Zhang; Ye He; Huijuan Wang (Journal of Environmental Radioactivity, 2024)

Microbiomic Analysis of Bacteria Associated with Rock Tripe Lichens from Alpine Areas in Eastern Alps and Equatorial Africa - Zichen He; Takeshi Naganuma; Ryosuke Nakai; Jun Uetake; Martin W. Hahn (Current Microbiology, 2024)
The diversity of bacteria associated with alpine lichens was profiled. Lichen samples belonging to the Umbilicariaceae family, commonly known as rock tripe lichens, were gathered from two distinct alpine fellfields: one situated on Mt. Brennkogel located in the Eastern European Alps (Austria), and the other on Mt. Stanley located in the Rwenzori mountains of equatorial Africa (Uganda). The primary aim of this research was to undertake a comparative investigation into the bacterial compositions, and diversities, identifying potential indicators and exploring their potential metabolisms, of these lichen samples. Bulk genomic DNA was extracted from the lichen samples, which was used to amplify the 18S rRNA gene by Sanger sequencing and the V3-V4 region of the 16S rRNA gene by Illumina Miseq sequencing. Examination of the fungal partner was carried out through the analysis of 18S rRNA gene sequences, belonging to the genus Umbilicaria ( Ascomycota ), and the algal partner affiliated with the lineage Trebouxia ( Chlorophyta ), constituted the symbiotic components. Analyzing the MiSeq datasets by using bioinformatics methods, operational taxonomic units (OTUs) were established based on a predetermined similarity threshold for the V3-V4 sequences, which were assigned to a total of 26 bacterial phyla that were found in both areas. Eight of the 26 phyla, i.e. Acidobacteriota , Actinomycota , Armatimonadota , Bacteroidota , Chloroflexota , Deinococcota , Planctomycetota , and Pseudomonadota , were consistently present in all samples, each accounting for more than 1% of the total read count. Distinct differences in bacterial composition emerged between lichen samples from Austria and Uganda, with the OTU frequency-based regional indicator phyla, Pseudomonadota and Armatimonadota , respectively. Despite the considerable geographic separation of approximately 5430 km between the two regions, the prediction of potential metabolic pathways based on OTU analysis revealed similar relative abundances. This similarity is possibly influenced by comparable alpine climatic conditions prevailing in both areas.

Thermo-enviro-economic analysis of a novel landfill gas-fueled CCHP-desalination process combined with a liquefied natural gas cold energy recovery unit - Zichen Xu; Ya-Jian Hu; Yu-Tao He; Tirumala Uday Kumar Nutakki; Asiful H. Seikh; V. Mohanavel; Nehad Ali Shah; Muxing Qin (Journal of Cleaner Production, 2024)

Nano-scale and micron-scale plastics amplify the bioaccumulation of benzophenone-3 and ciprofloxacin, as well as their co-exposure effect on disturbing the antioxidant defense system in mussels, Perna viridis - Junnan Li; Luhua You; Zichen Xu; Karina Yew-Hoong Gin; Yiliang He (Environmental Pollution, 2024)

Assessment of the depositional characteristics of the Yellow River estuary from 1960s by 239+240Pu and 137Cs - Yongjing Guan; Kaidi Fan; Shenzhen Wang; Liangjia Cui; Huijuan Wang; Zichen Guo; Wu Chen; Hua He; Zhiyong Liu (Science of The Total Environment, 2024)

Radioactivity research in mosses from typical Karst Regions in Leye Tiankeng, Southern China - Yongjing Guan; Qiaoyan Jing; Shenzhen Wang; Huijuan Wang; Wu Chen; Yuxin Hua; Zichen Guo; Liangjia Cui; Chunping Huang; Liang Wang; Pan Kuang; Xianwen He; et al. (Journal of Environmental Radioactivity, 2023)